Formação continuada de professores de ciências da natureza na rede estadual de São Paulo: há espaço para a alfabetização científica? - Almeida, Cyntia Helena Ravagnani de (Universidade Federal de São Carlos, 2023)
This research aimed to investigate the formative processes of educators in the field of natural sciences, conducted by the Education Department of the State of São Paulo (SEE). Considering the complexity of factors that permeate teacher training, in this work we will address issues related to continuous education with a focus on scientific literacy. We seek to understand the roles of teachers as subjects and schools as spaces for training, as well as to analyze the continuous training of teachers in the field of Natural Sciences in the years 2013, 2021, and 2022. We understand that teacher training involves a continuous process of professional development. In the context of this research, scientific literacy is investigated as part of the continuous formation of natural science teachers, implying not only the transmission of scientific knowledge but also the development of knowledge related to their pedagogical action. The methodology employed was document analysis, using documents and continuous training programs from the São Paulo State Education Department (SEE/SP). The documents are the videos of the Collective Pedagogical Work Activities available at the São Paulo Media Center, focusing on the theme of Sustainability. The guiding question was: "How does the continuous training promoted by the São Paulo State Education Department, in the years 2013, 2021, and 2022, incorporate scientific literacy and pedagogical rationalities in the context of scientific education?" Through the analysis of these materials, we sought to answer this question. In dialogue with theories about models of rationality in teacher training, we argue that the videos analyzed predominantly exhibit technical rationality, with a certain degree of depletion of concepts and discussions, without concern for developing in educators and students an awareness of practices that promote scientific literacy. Skills such as critical thinking, interactivity, and dialogue are left aside. Before the COVID-19 pandemic arrived in the country, teacher training in the state of São Paulo was conducted in person. In the face-to-face modality, there was direct interaction among participants, which enabled the exchange of experiences and life stories, as well as the establishment of professional contact networks and participation in practical activities. Even with the resumption of face-to-face activities in schools, training continued to be conducted remotely, maintaining the problems arising from this modality, mainly the lack of interaction among professionals.
Continuing education for natural science teachers in the state network of São Paulo: Is there room for scientific literacy?
Keywords: Ensino de ciências; Alfabetização científica; Educação dialógica; Educação científica; Formação continuada de professores; Science teaching; Scientific literacy; Dialogic learning; Science education; Continuing teacher education; CIENCIAS HUMANAS::EDUCACAO